Design and synthesis of new fluconazole analogues1. Issue 23 (21st June 2015) - Pore, Vandana S.; Agalave, Sandip G.; Singh, Pratiksha; Shukla, Praveen K.; Kumar, Vikash; Siddiqi, Mohammad I.
<x xml:space="preserve">Abstract</x> The synthesis of new fluconazole analogues containing two different 1, 2, 3-triazole units and an amide group is described. All the compounds showed very high antifungal activity and no toxicity.